2019
DOI: 10.2147/jpr.s188362
|View full text |Cite
|
Sign up to set email alerts
|

<p>Pharmacotherapeutic outcomes in atypical odontalgia: determinants of pain relief</p>

Abstract: Objectives There has been considerable research which has focused on clarifying the origin of pain in patients with atypical odontalgia (AO), also known as “idiopathic toothache”, and on identifying effective treatment, but there has been limited success so far. In this study, we assessed the outcomes of treatment and attempted to identify factors that could account for pain remission in patients with AO. Patients and methods Data for 165 patients diagnosed with AO from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 40 publications
(57 reference statements)
2
14
0
Order By: Relevance
“…This study also found the use of dopamine partial agonists (DPA), such as aripiprazole, effective for AO treatment. These findings are in accordance with the results of the research conducted by Tu et al, in which aripiprazole was used, both as a single dose or combined with TCA [7]. High dopamine tonic activities can increase pain due to the reduced release of μopioid [43].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This study also found the use of dopamine partial agonists (DPA), such as aripiprazole, effective for AO treatment. These findings are in accordance with the results of the research conducted by Tu et al, in which aripiprazole was used, both as a single dose or combined with TCA [7]. High dopamine tonic activities can increase pain due to the reduced release of μopioid [43].…”
Section: Discussionsupporting
confidence: 90%
“…High dopamine tonic activities can increase pain due to the reduced release of μopioid [43]. Therefore, aripiprazole, as a dopamine stabilization agent, can reduce pain intensity in patients diagnosed with AO [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As antidepressants are reported to be effective in the treatment of AO [1,3,2], the patient underwent medical treatment according to a combination therapy with fluoxetine and clonazepam suggested by Mortazavi et al, [2] Fluoxetine is a selective serotonin reuptake inhibitor (SSRI) antidepressant agent and clonazepam is a benzodiazepine derivative with anticonvulsant, muscle relaxant, analgesic, and anxiolytic properties [2]. Some other medications used for AO include gabapentin, tricyclic anti-depressants (TCAs), topical anesthetics, and opioids [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, there are very few medications formulated to specifically treat PIDP. As such, the first line medication for management of PIDP is a tricyclic antidepressant such as amitriptyline, which has been reported to successfully produce a 30% pain reduction in 65% of patients after 16 weeks 32 . SNRI (serotonin-norepinephrine reuptake inhibitors) such as milnacipran and duloxetine have also seen use.…”
Section: Managementmentioning
confidence: 99%